Gambaran Self-Compassion pada Wanita yang Pernah Mengalami Dating Violence: Sebuah Pendekatan Fenomenologi - Putri, Tiara Andini; Kurniawan, Rizal (ALSYS, 2024)
Dating violence is a form of abuse in a relationship that can have harmful physical and psychological impacts on one partner. Gender inequality due to patriarchal culture, along with the sense of attachment that often develops in women, makes them more vulnerable to becoming victims of dating violence. Self-compassion, which focuses on being kind to yourself and accepting pain as part of the human experience, can be used as a mechanism to help people cope with the traumatic experiences caused by dating violence. This study aims to describe self-compassion in women who have experienced dating violence using a qualitative method and a phenomenological approach. Data were collected through in-depth interviews, and purposive sampling was used to select 5 female participants, all of whom were college students who had experienced dating violence. Data analysis was carried out using a coding technique to identify the main themes related to the participants' self-compassion after experiencing dating violence. The findings showed that 2 out of 5 participants exhibited positive self-compassion. This was shown in their ability to recover after experiencing dating violence, where they could show care and concern for themselves during the difficult post-breakup phase while also giving themselves the necessary positive affirmations. Furthermore, the participants initiated productive activities to improve their self-worth and confidence. This positive self-compassion played an important role in facilitating the psychological and emotional recovery from the inner wounds caused by the abusive relationship.